The characteristics of brain network in patient with post-stroke depression under cognitive task condition - Peng, Yu; Zheng, Yang; Yuan, Ziwen; Guo, Jing; Fan, Chunyang; Li, Chenxi; Deng, Jingyuan; Song, Siming; Qiao, Jin; Wang, Jue (Frontiers in Neuroscience, 2023)
Objectives: Post-stroke depression (PSD) may be associated with the altered brain network property. This study aimed at exploring the brain network characteristics of PSD under the classic cognitive task, i.e., the oddball task, in order to promote our understanding of the pathogenesis and the diagnosis of PSD.Methods: Nineteen stroke survivors with PSD and 18 stroke survivors with no PSD (non-PSD) were recruited. The functional near-infrared spectroscopy (fNIRS) covering the dorsolateral prefrontal cortex was recorded during the conventional oddball task state and the resting state. The brain network characteristics were extracted using the graph theory and compared between the PSD and the non-PSD subjects. In addition, the classification performance between the PSD and non-PSD subjects was evaluated using features in the resting and the task state, respectively.Results: Compared with the resting state, more brain network characteristics in the task state showed significant differences between the PSD and non-PSD groups, resulting in better classification performance. In the task state, the assortativity, clustering coefficient, characteristic path length, and local efficiency of the PSD subjects was larger compared with the non-PSD subjects while the increased, and the global efficiency decreased inof the PSD subjects was smaller than that compared withof the non-PSD subjects.